APPLICATION OF ATTACHEMENT THEORY TO EQUINE-FACILITATED THERAPY - Aviva Vincent; Kathleen J. Farkas (Society Register)
Over the past two decades there has been a growing body of evidence, clinical and anecdotal, that equine-facilitated therapy (EFT) is a powerful tool for social workers and mental health clinicians. Recent research studies have begun to identify, name, and explain the mechanisms of EFT as a treatment tool for individual clients. However, EFT lacks a unified theoretical foundation; many studies lack an explicit theory altogether. Strong empirical support begins with a strong theoretical foundation, the research field lacks a unified voice for the scientific value of EFT. Attachment theory can guide the understanding of how EFT operates and can support more rigorous inquiry to evaluate its effect in mental health treatment. This article reviews the human-horse relationship in the context of attachment theory and concludes with a recommendation for research to strengthen the empirical base of EFT in social work practice.